’Guns don’t colonise people ...’: The role and use of firearms in pre-colonial and colonial Africa - Pilossof, Rory (Kronos: Southern African Histories, 2017)
This review essay examines a number of recent works that contribute to the history of firearms in colonial and pre-colonial Africa; two based upon new and original research (Story and Guy) and the others on reproductions of earlier seminal contributions to the historiography of firearms in Africa (Lamphear and Smaldone). Given the nature of firearms it is not surprising that the vast majority of literature on this technology focuses on their role in warfare and conflict. This is the primary concern of Smaldone 's work and the Lamphear collection. However, the scholarship on the role and use of firearms in Africa has undergone considerable changes over the last half-century and, given the dramatic transformations in political context within Africa over the same period, this is hardly surprising. Storey's contribution adds important depth to the study of firearms by examining a vast range of uses to which firearms were put in South Africa, as well as the numerous ways the colonial state sought to control the trade and possession of firearms. By discussing these works together, this essay explores what, if any, new developments have taken place in the historiography of firearms in colonial and pre-colonial Africa. While there are still some massive gaps in the literature, as this essay review exposes, the history of firearms in Africa should still be seen as an exciting field of study that has a great deal to offer potential researchers.